Effectiveness of the Paleo Diet on Weight-Loss among Individuals with Obesity: A Systematic Literature Review - Maryana, Nina; Nanda, Elma; Fadilah, Miftah (Inspirasi Foundation, 2026)
Introduction: Obesity has become a significant global public health issue. A variety of intervention strategies have been implemented, encompassing dietary modifications, physical activity, pharmacological treatments, and surgical procedures. Among these, the Paleolithic (Paleo) diet modeled after the presumed dietary patterns of humans during the Paleolithic era has attracted increasing scholarly attention as a potential nutritional approach for obesity management. Objective: This study aims to systematically review and evaluate the effectiveness of the Paleolithic (Paleo) diet in reducing body weight among individuals with obesity. Through an analysis of existing research, this review seeks to identify the benefits, limitations, and long-term sustainability of the Paleo diet as a weight management strategy. Method: This study aims to systematically review and evaluate the effectiveness of the Paleolithic (Paleo) diet in reducing body weight among individuals with obesity. Through an analysis of existing research, this review seeks to identify the benefits, limitations, and long-term sustainability of the Paleo diet as a weight management strategy. Results: A total of 880 participants were included across the seven reviewed studies. The findings revealed that the Paleo diet was effective in promoting weight loss among individuals with obesity. Participants who adhered to the Paleo diet for eight weeks experienced an average reduction of 5.3 kilograms in body weight. Conclusion: The Paleolithic diet (PD) is effective in reducing body weight, fat mass, and cardiometabolic risk factors compared with conventional diets, particularly in the short term. However, low adherence poses a major challenge, leading to diminished differences in benefits over the long term. Compared with the Mediterranean diet and intermittent fasting, adherence to PD is lower, and thus its long-term effectiveness requires further investigation.